Daclatasvir combined with sofosbuvir or simeprevir in liver transplant recipients with severe recurrent hepatitis C infection. Issue 4 (April 2016) - Fontana, Robert J.; Brown, Robert S.; Moreno‐Zamora, Ana; Prieto, Martin; Joshi, Shobha; Londoño, Maria‐Carlota; Herzer, Kerstin; Chacko, Kristina R.; Stauber, Rudolf E.; Knop, Viola; Jafri, Syed‐Mohammed; Castells, Lluís; et al.
Abstract : Daclatasvir (DCV) is a potent, pangenotypic nonstructural protein 5A inhibitor with demonstrated antiviral efficacy when combined with sofosbuvir (SOF) or simeprevir (SMV) with or without ribavirin (RBV) in patients with chronic hepatitis C virus (HCV) infection. Herein, we report efficacy and safety data for DCV‐based all‐oral antiviral therapy in liver transplantation (LT) recipients with severe recurrent HCV. DCV at 60 mg/day was administered for up to 24 weeks as part of a compassionate use protocol. The study included 97 LT recipients with a mean age of 59.3 ± 8.2 years; 93% had genotype 1 HCV and 31% had biopsy‐proven cirrhosis between the time of LT and the initiation of DCV. The mean Model for End‐Stage Liver Disease (MELD) score was 13.0 ± 6.0, and the proportion with Child‐Turcotte‐Pugh (CTP) A/B/C was 51%/31%/12%, respectively. Mean HCV RNA at DCV initiation was 14.3 × 6 log10 IU/mL, and 37% had severe cholestatic HCV infection. Antiviral regimens were selected by the local investigator and included DCV+SOF (n = 77), DCV+SMV (n = 18), and DCV+SMV+SOF (n = 2); 35% overall received RBV. At the end of treatment (EOT) and 12 weeks after EOT, 88 (91%) and 84 (87%) patients, respectively, were HCV RNA negative or had levels <43 IU/mL. CTP and MELD scores significantly improved between DCV‐based treatment initiation and last contact. Three virological breakthroughs and 2 relapses occurred in patients treated with DCV+SMV with or without RBV. None of the 8 patient deaths (6 during and 2 after therapy) were attributed to therapy. In conclusion, DCV‐based all‐oral antiviral therapy was well tolerated and resulted in a high sustained virological response in LT recipients with severe recurrent HCV infection. Most treated patients experienced stabilization or improvement in their clinical status. Liver Transplantation 22 446‐458 2016 AASLD